Exploring transcendence of the quantum self and consciousness through communication symbols - Rose-Marié Bezuidenhout (Communicare)
This study is an exploration of how the quantum self, the quintessence of the individual, draws on archetypal symbols and mythologems during the process of intrapsychic communication. The process relates to the confluence of a subjective, inner experiential reality and reality as a social construct during transcendent cycles of the unique individual. The Jungian constructs of archetypal images, symbols, myths and mythologems are considered as the derivatives of this subjective, inner reality reflected in the text of a narrative and the dreams of an individual. An archetypal and mythical semiotic textual analysis of ‘The Alchemist’ by Paolo Coehlo, and an individual case analysis of dream symbols and a self-report based on the interpretation of a dream theme by using active imagination indicate that an inner, subjective transcendental reality is imminent in the individual. An intrinsic need for and representation of equanimity and unity are reflected in the images, symbols and myths of the self as archetype of meaning nested in the collective unconscious.